Geographical ecology and conservation of Eugenia L. (Myrtaceae) in the Brazilian Cerrado: Past, present and future - Oliveira, Hauanny Rodrigues; Staggemeier, Vanessa G. [UNESP]; Quintino Faria, Jair Eustáquio; de Oliveira, Guilherme; Diniz-Filho, José Alexandre F. (My University, 2018)
Human actions have caused the fragmentation of natural vegetation, habitat loss and climate change. The Cerrado, considered one of the global hotspots of diversity, has suffered great habitat loss due to these factors, which has been aggravated by the agricultural expansion that took place during the last 60 years. In this context, we chose species of the genus Eugenia L. (Myrtaceae) occurring in the Brazilian Cerrado to describe richness patterns and range loss, and determine conservation priorities for the Cerrado. Ecological niche models (ENMs) were applied to calculate the geographical range of each species in the past (Last Glacial Maximum – LGM, 21 000 years ago), present (PIP, representing current climatic conditions – 1760 years ago) and future (near future – NF, 2080–2100). These results were combined to calculate the richness of the group and also to estimate the range loss of these species in the future. Moreover, we evaluated the irreplaceability of areas for species conservation, aiming to maximize the biotic stability of Eugenia species. Our results showed that the highest species richness in the past was found in the southwestern region of the Cerrado and, currently, the richest regions are found in the central and southeastern areas. However, in the future, we predict a shift of the greatest values of richness towards the southeastern region, an area currently occupied by the Atlantic forest. Although areas with high conservation priorities were found scattered across the biome, this shift is worrisome due to the high fragmentation rate and intensive human occupation thoughout the Atlantic region. Thus, conservation efforts should focus on areas found within these limits.
Keywords: climate change; ecological niche models; habitat fragmentation; herbarium data; irreplaceability